Biomechanical and biophysical environment of bone from the macroscopic to the pericellular and molecular level. (October 2015) - Ren, Li; Yang, Pengfei; Wang, Zhe; Zhang, Jian; Ding, Chong; Shang, Peng
Abstract: Bones with complicated hierarchical configuration and microstructures constitute the load-bearing system. Mechanical loading plays an essential role in maintaining bone health and regulating bone mechanical adaptation (modeling and remodeling). The whole-bone or sub-region (macroscopic) mechanical signals, including locomotion-induced loading and external actuator-generated vibration, ultrasound, oscillatory skeletal muscle stimulation, etc ., give rise to sophisticated and distinct biomechanical and biophysical environments at the pericellular (microscopic) and collagen/mineral molecular (nanoscopic) levels, which are the direct stimulations that positively influence bone adaptation. While under microgravity, the stimulations decrease or even disappear, which exerts a negative influence on bone adaptation. A full understanding of the biomechanical and biophysical environment at different levels is necessary for exploring bone biomechanical properties and mechanical adaptation. In this review, the mechanical transferring theories from the macroscopic to the microscopic and nanoscopic levels are elucidated. First, detailed information of the hierarchical structures and biochemical composition of bone, which are the foundations for mechanical signal propagation, are presented. Second, the deformation feature of load-bearing bone during locomotion is clarified as a combination of bending and torsion rather than simplex bending. The bone matrix strains at microscopic and nanoscopic levels directly induced by bone deformation are critically discussed, and the strain concentration mechanism due to the complicated microstructures is highlighted. Third, the biomechanical and biophysical environments at microscopic and nanoscopic levels positively generated during bone matrix deformation or by dynamic mechanical loadings induced by external actuators, as well as those negatively affected under microgravity, are systematically discussed, including the interstitial fluid flow (IFF) within the lacunar–canalicular system and at the endosteum, the piezoelectricity at the deformed bone surface, and the streaming potential accompanying the IFF. Their generation mechanisms and the regulation effect on bone adaptation are presented. The IFF-induced chemotransport effect, shear stress, and fluid drag on the pericellular matrix are meaningful and noteworthy. Furthermore, we firmly believe that bone adaptation is regulated by the combination of bone biomechanical and biophysical environment, not only the commonly considered matrix strain, fluid shear stress, and hydrostatic pressure, but also the piezoelectricity and streaming potential. Especially, it is necessary to incorporate bone matrix piezoelectricity and streaming potential to explain how osteoblasts (bone formation cells) and osteoclasts (bone resorption cells) can differentiate among different types of loads. Specifically, the regulation effects and the related mechanisms of the biomechanical and biophysical environments on bone need further exploration, and the incorporation of experimental research with theoretical simulations is essential. Highlights: The biomechanical and biophysical environment of bone is significantly different at different anatomical levels. Bending and torsion deformation of load-bearing long bone during locomotion can generate strain, interstitial fluid flow, hydrostatic pressure, piezoelectricity and streaming potential. These biomechanical and biophysical environments must act in conjunction in regulating bone adaptation.